Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
Thomas M. Carr, Jr, Dramatic structure and philosophy in Brutus, Alzire and Mahomet George A. Perla, Zadig, hero of the absurd David E. Highnam, L'Ingénu: flawed masterpiece or masterful innovation P. Emeka Abanime, Voltaire as an anthropologist: the case of the albino Theodore Besterman, Some eighteenth-century Voltaire editions unknown to Bengesco: supplement to the fourht edition. Lawrence J. Forno, The Cosmic mysticism of Diderot Manfred Kusch, Manon Lescaut, or voyage du chevalier Des Grieux dans la basse Romancie Louis A. Olivier, Bachaumont the chronicler: a questionable renown Donald T. Siebert, Jr, The Uses of adversity: Soame Jenyn's debt to Johnson Review. The New Diderot edition, by Theodore Besterman